OP0112 UNACCEPTABLE PAIN DESPITE INFLAMMATION CONTROL AFTER START OF A FIRST ANTI-TNF THERAPY IN PATIENTS WITH PSORIATIC ARTHRITIS AND ITS RELATION TO TREATMENT RESPONSE. (June 2019) - Roseman, Carmen; Wallman, Johan K; Jöud, Anna; Schelin, Maria; Einarsson, Jon T; Lindqvist, Elisabet; Kapetanovic, Meliha C; Lampa, Jon; Olofsson, Tor
Abstract : Background: Pain is a major concern of patients with inflammatory arthritides, but while considerable focus has been put on the occurrence and management of pain due to inflammation, less is reported on pain despite inflammation control, with most such reports addressing rheumatoid arthritis (RA). Objectives: To investigate the prevalence of pain despite inflammation control after start of a first anti-TNF therapy in psoriatic arthritis (PsA) patients and its relation to EULAR treatment response. To test the feasibility of a network analysis approach to examine associations between clinical variables and mental health symptoms in RA. Methods: PsA patients starting a first anti-TNF therapy 2004-2010 were identified in the prospective, observational South Swedish Arthritis Group register (n= 352, 48% women), with mean age 47 years and mean disease duration 10 years. At anti-TNF start, 63% of patients had ongoing methotrexate and 68% were on any conventional DMARD(s). Based on the patient acceptable symptom state (PASS)1, unacceptable pain was defined as >40 mm on a Visual Analogue Scale (VAS) of pain (scale 0-100 mm), and concomitant inflammation control (as in earlier RA studies) was captured through CRP<10 mg/L, 2 in combination with <1 swollen joint (of 28).3 Assessments were performed at baseline, 1.5, 3, 6 and 12 months after anti-TNF start. Furthermore, analyses were conducted in relation to EULAR treatment response after 3 months (good, moderate, no response). Differences in pain measures between treatment response groups were estimated by logistic regression. Results: At start of a first anti-TNF therapy, 84.5% of PsA patients reported unacceptable pain, which declined to 42.9% after 3 months and then remained stable during the rest of the study period, being 39.5% at 12 months (Figure 1A). In contrast, the fraction showing unacceptable pain despite inflammation control was largely unchanged over the study period (24.0 % at treatment start, 26.7% at 3 months and 26.2% at 12 months). Unacceptable pain at 3 months was strongly related to EULAR 3-month response (23.7% of good responders vs. 70.8% of non-responders; p<0.001), whereas for unacceptable pain despite inflammation control the relation was less pronounced (19.3% of EULAR good responders vs 37.5% of non-responders, p=0.016). Among EULAR good responders, unacceptable pain despite inflammation control constituted 81% of all unacceptable pain at 3 months (Figure 1B). Conclusion: A considerable proportion of PsA patients starting their first biological treatment reported unacceptable pain throughout the first treatment year. Among EULAR good responders non-inflammatory pain made up more than 4/5 of this pain load at 3 months, indicating insufficient effects of biologics on a subset of patients with inflammation-independent pain, and strongly warrants alternative treatment strategies in affected patients. References: [1] Tubach et al. Arthritis Care Res 2012;64:1699-72. [2] Lourdudoss et al. Arthritis Care Res. 2018;70:205-12. [3] Olofsson et al. Ann Rheum Dis 2018;77:S2. Acknowledgement: Associate professor Pierre Geborek Disclosure of Interests: Carmen Roseman: None declared, Johan K Wallman Consultant for: Consultant for AbbVie, Celgene, Eli Lilly, Novartis, and UCB Pharma., Anna Jöud: None declared, Maria Schelin: None declared, Jon T Einarsson: None declared, Elisabet Lindqvist: None declared, Meliha C Kapetanovic: None declared, Jon Lampa Grant/research support from: Abbvie, Consultant for: Eli Lilly, Sandoz, Tor Olofsson: None declared